Tips and tidbits a book for family day care providers - Gonzalez-Mena, Janet; National Association for the Education of Young Children (Washington, DC National Association for the Education of Young Children, 1991)
Practical information and advice to help solve problems in a concrete way.
Keywords: Family day care; Behavior modification; Child care; Day care centers; Education, Preschool